Trends and Developments in Religious Psychology Research Methods: A Bibliometric Study of SCOPUS Publications (2015–2025) - Hamdi, Hamdi; Hamdanah, Hamdanah; Hartati , Zainap; Huda, Ali Anhar Syi’bul (Al Ulya: Jurnal Pendidikan Islam, 2025)
This study is motivated by the growing need for a systematic examination of research methods in the psychology of religion, a field still largely dominated by quantitative approaches and lacking integration of qualitative and interdisciplinary perspectives. As research paradigms shift toward more contextual and phenomenological orientations, a comprehensive mapping of methodological trends has become essential. The purpose of this study is to analyze the trends, sources, and themes of scientific publications on research methods in the psychology of religion during the 2015–2025 period and to provide recommendations for future methodological development. Using a quantitative bibliometric approach, 160 publications were collected from the Scopus database and analyzed with Publish or Perish, VOSviewer, and Microsoft Word through a descriptive qualitative lens. The findings reveal a significant increase in publication volume, peaking in 2025, although only 44.4% directly address the core topic of psychology of religion. Most publications (93.1%) appeared in academic journals, indicating the dominance of digital dissemination in scientific communication. Analysis of active contributors identified five researchers from different countries, reflecting the field’s global and interdisciplinary nature. The keyword “religion” appeared most frequently, whereas “qualitative study” remained peripheral and insufficiently integrated into the main discourse. The study highlights the need to strengthen qualitative approaches within the psychology of religion to deepen understanding of subjective experience, personal meaning, and spiritual dimensions more holistically.